Bioplastic sheet production from 1,3-Propanediol produced by raw Glycerol fermentation - Pattanasupong, Anchana; Tungsatitporn, Sirorat; Meeploy, Sutthirak; Wangdeetham, Rommanee (Asia-Pacific Journal of Science and Technology, 2017)
1,3-Propanediol (PDO) was produced by Enterobacter radicincitans TISTR 1805 using crude glycerol fermentation for bioplastics sheet production. PDO production was scaled up to 150 L in a 300 L pilot scale fermentor by 5% crude glycerol at 37 ºC during 3 days. The PDO yield was 344.3 mmol mol-1 pure glycerol and the cell growth rate was 8.1-28.8 mg L-1 hr-1. After that, the culture product was passed through purification process by diatomite filtration and fractional distillation at the range of 150-300 ºC, using the pressure of 10 mmHg. The purity of PDO was 98%. Preparation of polypropylene succinate (PPSu) using PDO was carried out by esterification and polycondensation processes. Then, the PPSu was blended with cellulose acetate and casted for bioplastic film. The preliminary result of biodegradation test in compost revealed that this film could be degraded 69-85% within 3 months at 58±2 ºC incubation. Furthermore, studies on primary testing of toxicity of residues after degradation on a tested animal, Daphnia magna, and a tested plant, Brassica chinensis, were also performed.